The value of a good idea : protecting intellectual property in an information economy. - Loberg, Kristin (Taking control series., 2004)
The popularity of the Internet has seen an explosion in disputes over intellectual property issues. This book gives business people the tools for fighting these battles effectively. Starting with a review of the legal concepts that define intellectual property, this book offers clear and useful insights into how these concepts work in the real world. It explains complex (even to legal experts) issues like fair use, infringement, joint authorship and permissions in terms that lay people can comprehend. Readers will understand how to build and protect commercial ideas ... and how to use existing o.